Research Progress of Lipid Metabolism Reprogramming in Prostate Cancer - ZENG Kai; LIU Jihong; LI Qiang; WANG Qinzhang (Zhongliu Fangzhi Yanjiu, 2022)
Metabolism reprogramming plays an important role in the process of tumor occurrence and development, and provides the necessary material basis for tumor cells. It can change the metabolic patterns of amino acids, glucose and fatty acids in tumor cells, which is one of the hallmark features of tumors. At present, it is shown that most tumors tend to take advantage of glycolysis for energy resource. In contrast, studies have shown that prostate cancer cells dependent more on the fatty acid oxidation pathway for metabolic reprogramming to obtain energy substances. Therefore, it is of great significance to understand the relation between key enzymes of lipid metabolism and regulatory genes for early diagnosis, targeted treatment and better prognosis of prostate cancer.